Analisis Rasio Profitabilitas Pada PT. Wijaya Karya Beton Tbk - Siregar, Rodizah; Syafina, Laylan (Lembaga Riset Ilmiah, 2022)
The purpose of this study was to determine the financial performance of PT. Wijaya Karya Beton Tbk. If measured based on the Profitability Ratio. This type of research uses secondary data sourced from financial reports from 2018-2020. The results of the analysis show that the financial performance is still not good, because it is still below the average industry standard. Judging from the NPM, ROA and ROE, its financial performance is still not good because the value achieved is still below the standard average. The purpose of this study is to determine the financial performance of PT. Wijaya Karya Beton Tbk. If measured based on the Profitability Ratio. This type of research uses secondary data sourced from financial reports from 2018-2020. The results of the analysis show that the financial performance is still not good, because it is still below the average industry standard. Judging from the NPM, ROA and ROE, its financial performance is still not good because the value achieved is still below the standard average